(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Tennis Elbow is the most common overuse syndrome in the elbow. It is a tendinopathy injury involving the extensor muscles of the forearm. The lateral epicondylitis is characterized by pain and tenderness at the lateral epicondyle of the humerus as there is non-specific inflammation at the origin of the extensor muscles of forearm. As there is pain and inflammation, the grip strength in decreased and hand function is affected. But there are few research done on intervention regarding same. Hence a comparative study was carried on 60 patient, 30 subjects were grouped in Group A which were given functional task exercises and Group B was given Conventional therapy. The stastical analysis showed that out of 30 subjects, mean age of group A patients was 25±6.23 and mean age of group B patients was 27.2±4.8. Grip strength in between Group A (63.5± 14.2) and Group B (60.4± 12.9) with p value 0.04, Patient rated tennis elbow evaluation scale in between Group A (44.1± 6.8) and Group B (43.8±10.6) with p value 0.002 and Michigan hand outcome measures in between Group A (62.5±14.4) and Group B (54.3±14.7) with p value 0.0005. Hence the study concluded that there is significant effect of Functional Task Exercises on Grip strength and Hand function in lateral epicondylitis.